The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.ultrasmedbio.2015.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Toward 3-D Echocardiographic Determination of Regional Myofiber Structure

Abstract: As a step toward the goal of relating changes in underlying myocardial structure to observed altered cardiac function in the hearts of individual patients, this study addresses the feasibility of creating echocardiography-derived maps of regional myocardial fiber structure for entire, intact, excised sheep hearts. Backscatter data were obtained from apical echocardiographic images acquired with a clinical ultrasonic imaging system and used to determine local fiber orientations in each of seven hearts. Systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Previously, we validated that apparent ultrasonic backscatter could be used to map myofiber architecture in human-size sheep hearts using a clinical imaging system (Milne, et al 2016). The increase in pre-clinical studies, including a number of rat models of heart failure, suggest numerous opportunities to apply this method in rodents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we validated that apparent ultrasonic backscatter could be used to map myofiber architecture in human-size sheep hearts using a clinical imaging system (Milne, et al 2016). The increase in pre-clinical studies, including a number of rat models of heart failure, suggest numerous opportunities to apply this method in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Mean and standard deviation of each of the seven hearts were calculated for each data acquisition mode. Previous work indicated that the relationship between apparent backscatter and fiber angle may be empirically modeled by a function of even powers of sines and cosines (Milne, et al 2012, Milne, et al 2016, Mottley and Miller 1988). Based on these works and our fits of individual and mean data, the mean data was fit to the following function: …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that measuring myofiber-direct strain, as opposed to principal ventricular axis strains, might help design mechanical experiments that would better mimic physiologic myofiber strains and strain rates, including in the context of increased fibrosis common in diastolic dysfunction [30,34]. Myofiber strain is more complicated to measure because MRI or ultrasound techniques must be used to first measure the helical myofiber architecture [10,55,56]. These measures might validate predictions from ex vivo studies.…”
Section: A Translational Perspective On Myocardial Motionmentioning
confidence: 99%
“…Registration errors also contribute to angle discrepancies. In sheep hearts, the average angle difference between two scans of the same heart was found to vary by nearly 10 degrees, mostly due to registration error [2]. Acute angle error (AAE) has been used as a common approach to quantify angle differences.…”
Section: Introductionmentioning
confidence: 99%